2017
DOI: 10.5539/elt.v11n1p179
|View full text |Cite
|
Sign up to set email alerts
|

No English Learner Left Behind: How Can States and Teacher Preparation Programs Support Content-Area Practitioners?

Abstract: This study investigates the responses that education stakeholders give to regular teacher and teacher candidate professional needs because of the increasing number of English learners. Two major research questions related to the increase of English learners in US schools and to the responses that stakeholders have provided guided the inquiry. Using a case study approach, the results show that not only have the numbers of English learners risen, but also that some school districts have witnessed drastic demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This type of questioning has been referred to as scaffolded questions and tiered questions (Hill & Flynn, 2006). The current study assumes leveled questions (LQs) as described by Nutta and colleagues (2014;2018). Leveled questions provide opportunities for teachers to realize whether ELs' responses are limited due to their overall understanding of the content or their EPL (Nutta et al, 2018).…”
Section: Scaffolding Questions For Elsmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of questioning has been referred to as scaffolded questions and tiered questions (Hill & Flynn, 2006). The current study assumes leveled questions (LQs) as described by Nutta and colleagues (2014;2018). Leveled questions provide opportunities for teachers to realize whether ELs' responses are limited due to their overall understanding of the content or their EPL (Nutta et al, 2018).…”
Section: Scaffolding Questions For Elsmentioning
confidence: 99%
“…Teachers need to understand effective strategies for teaching ELs (de Jong & Harper, 2005). Similar to Diarrassouba (2018) and Wissink and Starks (2019), Regalla and colleagues (2016) found that teacher candidates (TCs) have reported their teacher preparation programs still left them feeling unprepared to instruct the ELs in their prospective classrooms. Hence, communication barriers can be reduced when teacher preparation programs focus on meeting the needs of ELs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation